Industry Real-Life Accounting Practice: A Differential Effect on Accounting Students’ Performance - Ngwakwe, Collins C (South African Journal of Higher Education, 2016)
This paper presents an evaluation of potential differential effect of video presentation of industry real-life practice of Management Accounting on the academic performance of accounting students. The methodological approach used is a study of final year Bachelor of Commerce (BCom) accounting students in a South African University. An accounting video of industry real-life application of Management Accounting systems were shown to students on two modules (in an alternating manner) after completing the lectures; this was followed by four concept tests; in an alternating approach. Using a statistical t-test of difference in means; findings show a significant difference between the two scenario concept tests. The paper offers agenda for further research using other accounting courses and also to apply this in different levels of accountancy study and using other universities in the Republic.